Green Purchasing Practices and Environmental Performance - Ai Chin Chin Thoo; Nurul Farah Izzati Ab Malik; Hon Tat Huam; Zuraidah Sulaiman; Liat Choon Tan (International Journal of Supply Chain Management, 2020)
Green purchasing aims to minimize negative environmental impacts in manufacturing process and transportation by using durable, recyclable and reusable materials. This study aims investigate the impact of green purchasing practices including green product, green process and green supplier on environmental and business performance in the context of Malaysian manufacturing companies. A total of 156 questionnaires were distributed to different industry sectors. The findings show that green product, green process and green supplier are significantly and positively related to environmental performance. In addition, green product is the main predictor of the environmental performance. Ultimately, the results could offer useful guidance for green purchasing practices implementation in Malaysian manufacturing companies and provide a springboard for further empirical research in the area.